Correlation analysis between CD133, Klk3 and grhl2 expression and tumor characteristics in prostate cancer - Wu, Jinhua; Guo, Shulin; Wang, Luxia; Liao, Zhongxiang (Cellular and Molecular Biology, 2022)
Prostate cancer is a common clinical disease in men. It is known that prostate cancer ranks 3rd in the incidence of malignant tumors of the male genitourinary system in China, which is able to evaluate the riskiness of life expectancy of male patients. Therefore, we investigated the expression of CD133, recombinant human kallikrein 3 (Klk3), grainy head like 2 (grhl2) in prostate cancer, and correlation with tumor characteristics in the present study. A total of 167 prostate cancer patients who underwent surgical treatment in our hospital from February 2017 to April 2021 were selected. Their cancer and adjacent tissues were resected, and CD133 was detected by double staining using immunohistochemistry, Klk3 and grhl2 were detected by RT-PCR analysis, and CD133, Klk3 were analyzed by Pearson's method in different clinical stages, Gleason grade Correlation of grhl2 with tumor characteristics. The expression of CD133, KLK3, and GRHL2 in cancer tissue was increased compared with adjacent tissue (P < 0.05). The expression of CD133, KLK3, and GRHL2 increased with the aggravation of the clinical stage and Gleason grade (P < 0.05). CD133, KLK3, and GRHL2 showed a positive correlation in prostate cancer. The Pearson method found a positive correlation between CD133, KLK3, GRHL2 and clinical stage, Gleason grade, and lymph node metastasis. In general, high CD133, Klk3, and grhl2 expression was observed in prostate cancer and increased with the disease. They presented a positive correlation in prostate cancer presence, and these three gene products correlated with tumor characteristics.